2020
DOI: 10.5334/gh.364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on Complications, Long Term Mortality and Recurrence in 608,890 Hospitalised Patients with Stroke

Abstract: Background: Patients with diabetes mellitus (DM) have been found to be at an increased risk of suffering a stroke. However, research on the impact of DM on stroke outcomes is limited. Objectives: We aimed to examine the influence of DM on outcomes in ischaemic (IS) and haemorrhagic stroke (HS) patients. Methods: We included 608,890 consecutive stroke patients from the Thailand national insurance registry. In-hospital mortality, sepsis, pneumonia, acute kidney injury (AKI), urinary tract infection (UTI) and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 43 publications
5
20
0
1
Order By: Relevance
“…Diabetes is not only associated with stroke but also with risk of adverse stroke outcome 9,10 . In a study of hospital complications with stroke in Thailand, diabetes was associated with increased risk of sepsis and acute kidney injury, and to a lesser extent with cardiovascular events, with pneumonia and urinary infection, and with in‐hospital mortality 21 . Diabetes increases the likelihood of stroke recurrence, 22 and diabetes, but not prediabetes, has been reported to be associated with increased risk of developing cognitive impairment and dementia, particularly that occurring after stroke 23 …”
Section: The Association Of Diabetes With Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is not only associated with stroke but also with risk of adverse stroke outcome 9,10 . In a study of hospital complications with stroke in Thailand, diabetes was associated with increased risk of sepsis and acute kidney injury, and to a lesser extent with cardiovascular events, with pneumonia and urinary infection, and with in‐hospital mortality 21 . Diabetes increases the likelihood of stroke recurrence, 22 and diabetes, but not prediabetes, has been reported to be associated with increased risk of developing cognitive impairment and dementia, particularly that occurring after stroke 23 …”
Section: The Association Of Diabetes With Strokementioning
confidence: 99%
“…9,10 In a study of hospital complications with stroke in Thailand, diabetes was associated with increased risk of sepsis and acute kidney injury, and to a lesser extent with cardiovascular events, with pneumonia and urinary infection, and with inhospital mortality. 21 Diabetes increases the likelihood of stroke recurrence, 22 and diabetes, but not prediabetes, has been reported to be associated with increased risk of developing cognitive impairment and dementia, particularly that occurring after stroke. 23 An important cause of stroke is atrial fibrillation, and in a study of this relationship, persons with diabetes, although more likely to be anticoagulated with warfarin than nondiabetic persons with atrial fibrillation, had greater risk of stroke, although with improvement during the period from 1992 to 2019.…”
Section: The Association Of Diabetes With Strokementioning
confidence: 99%
“…Compared with nondiabetic patients, diabetic patients have poor functional outcome, worse long-term vascular prognosis, and higher mortality after stroke onset [5]. However, given the inconsistent associations found in previous investigations, no consensus has been reached on the role of diabetes in the occurrence of hemorrhagic stroke (HS) [6][7][8][9][10][11]. Some studies reported no significant relationship between diabetes and HS [7,8], while others showed a significant and positive association [9,10] or found that HS occurs significantly less frequently in patients with diabetes [11].…”
Section: Introductionmentioning
confidence: 99%
“…As has been previously reported by other authors those suffering diabetes have a higher number of cardiovascular risk factors and concomitant chronic diseases [ 24 , 25 ]. Therefore, the IHM and long-term mortality rate in ischemic stroke patients with diabetes are 1.13-fold and 1.52-fold higher than in those without diabetes [ 26 ]. In addition, as expected, and consistent with findings reported before, older age, renal disease, atrial fibrillation, congestive heart failure, acute myocardial infarction, and dementia are risk factors for IHM [ 12 , 13 , 16 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, no information is available in the SNHDD to evaluate the distribution of Trial of Org 10172 in Acute Stroke Treatment (TOAST) subtype of stroke, nor to quantify stroke severity using the National Institute of Health Stroke Scale/Score (NIHSS) or the degree of disability at discharge in our epidemiological study. However, administrative databases using the ICD coding system have been previously used to investigate stroke in Spain and other countries [ 11 , 12 , 13 , 14 , 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%